2019
DOI: 10.32861/jssr.54.1311.1320
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Investment Decision Making: Moderating Role of Investors Characteristics

Abstract: The current study aimed to investigate the factors affecting investment decision making. Moreover, the moderating effects of age, gender, and financial information were also tested. The study utilized a quantitative research design for that the data was collected using a structured questionnaire. The questionnaire was sent to 570 individuals out of that 374 questionnaires were returned however 372 of the questionnaires were found to be useable. The study framework had 6 constructs namely heuristics, financial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…According to (A. Alshamy, 2019), overconfidence was also important in making better investment decisions on the Pakistan Stock Exchange. According to (Saurabh & Nandan, 2020) Pakistani investors are significantly and positively influenced by overconfidence on investment decisions.…”
Section: Theoretical Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…According to (A. Alshamy, 2019), overconfidence was also important in making better investment decisions on the Pakistan Stock Exchange. According to (Saurabh & Nandan, 2020) Pakistani investors are significantly and positively influenced by overconfidence on investment decisions.…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…This is because there will be factors or assumptions that influence investment decision-making when making investment decisions (A. Alshamy, 2019). Mental accounting is included in prospect theory, which explains that the state of mind can affect the investor's decisionmaking process; investors tend to categorise their finances in different accounts that deviate from conventional concepts, causing irrational effects on investment decisions.…”
Section: Theoretical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Alquraan et al (2016) found that loss aversion has a positive impact on investment decisions, while risk perception has a negative impact, since investors in high-risk situations often withdraw from investing, in order to minimize losses due to uncertainty of return. Alshamy (2019) concluded that risk aversion positively affects investment decisions. According to Luong and Thu Ha (2011), prospect theory elements negatively affect investment performance, because of a different perception about gains and losses.…”
Section: Prospect Theorymentioning
confidence: 99%
“…An interesting fact was revealed from extensive survey research conducted by Lan et al (2018), where demographic characteristics, such as age, gender, years of education, occupation, investment experience, financial knowledge level, and income, are closely linked to decision behaviors. Alshamy (2019) employed structural equation modeling to show that expertise, risk aversion, corporate governance, financial information, and experience to be significant determinants affecting investment decision making, in addition to gender, age, and financial education as moderating variables. A study by Schwarzkopf (2003) revealed that the attraction effect, i.e., an effect that occurs in which adding an inferior or irrelevant alternative into an existing choice set changes decision maker's perception due to its ability to increase the attractiveness, can influence investment decisions.…”
Section: Introductionmentioning
confidence: 99%